PENGARUH BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), NON PERFORMING LOAN (NPL) DAN NET INTEREST MARGIN (NIM) TERHADAP PROFITABILITAS PADA BANK UMUM KEGIATAN USAHA (BUKU) 4 PERIODE 2018-2022 - Dian Putri Kesumastuti; Alean Kistiani Hegy Suryana; Nur Asih Triatmaja (JURNAL EKONOMI, 2023)
This study aims to analyze the significance of the effect of the BOPO, NPL and NIM ratios partially on profitability at Commercial Banks for Business Activities (BUKU) 4 Period 2018-2022. The population in this study is Commercial Bank Business Activities (BUKU) 4. The sampling technique uses saturated sampling method. The data used in this study is secondary data obtained from published financial reports at the Financial Services Authority (OJK). The data analysis model uses the Multiple Linear Regression Analysis Model, while the data analysis technique uses the F Test, The Coefficient of Determination (R²) and the t Test. The results of the analysis and discussion show that the variable Operating Income Operating Costs (BOPO) partially has a significant effect on Profitability, Non Performing Loan (NPL) variables partially has a significant effect on Profitability, while the Net Interest Margin (NIM) variable partially has a significant effect on Profitability in Commercial Bank Business Activities (BUKU) 4 Period 2018-2012.